Trichoblastoma Arising From the Nevus Sebaceus of Jadassohn - Chahboun, Fatimazahra (Cureus, 2021)
Trichoblastoma is a rare benign skin adnexal tumour, belonging to the category of trichogenic tumours. The clinical and histological findings may often be confused with basal cell carcinoma, a malignant epidermal skin tumour. We report here a case of a 70-year-old man presented with a dome-shaped, dark-pigmented nodule within a yellowish hairless plaque on the scalp. The plaque had existed since childhood. However, the central pigmented nodule began appearing three months ago and enlarging gradually. The patient had no medical history. Furthermore the physical examination revealed a translucent, verrucous, and yellowish plaque, with central and pigmented nodule measuring 0.7 × 0.5 cm. Also basal cell carcinoma and trichoblastoma’s diagnosis were discussed. The patient was subsequently referred to the plastic surgery department, where he underwent a total excision. The histological examination was in favour of trichoblastoma arising from the nevus sebaceus. After 24 months of checking, no recurrence was observed. Trichoblastoma is a benign adnexal tumour. Its progression to malignant trichoblastoma (or trichoblastic carcinoma) is possible, but remains exceptional. Therefore, complete excision should be proposed to the patient at the time of diagnosis.